SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2118/30488-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drill Pipe Rotation Effects on Frictional Pressure Losses in Slim Annuli

Abstract: Drill Pipe Rotation Effects on Frictional Pressure Losses in Slim Annuli. SPE-member Abstract The effect of rotation on the frictional pressure loss in an annulus has been studied experimentally. A direct comparison with results obtained with a 3D CFD (computational fluid dynamics) code has been performed for laminar flow. Experimental results for three fluids are presented. In this paper we will focus on two effects of rotation in a slim hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Hansen et al (1999) and Sterri et al (2000) observed that pressure drop increases with the increase in drill string rotation while the reverse behavior was reported by Hansen and Sterri (1995). In our case, we observed an increase in the pressure drop with the increase of drill string rotational speed, which is in accordance with most field observations.…”
Section: Momentum Balance Givessupporting
confidence: 91%
“…Hansen et al (1999) and Sterri et al (2000) observed that pressure drop increases with the increase in drill string rotation while the reverse behavior was reported by Hansen and Sterri (1995). In our case, we observed an increase in the pressure drop with the increase of drill string rotational speed, which is in accordance with most field observations.…”
Section: Momentum Balance Givessupporting
confidence: 91%
“…Numerous laboratory studies (Nouri and Whitelaw 1994;Hansen and Sterri 1995;Hansen et al 1999;Ahmed and Miska 2008;Yamada 1962;Walker and Al-Rawi 1970;Wei 1997;Woo et al 2005) were carried out to evaluate the effect of pipe rotation on annular pressure loss. Most of these studies demonstrate both negative and positive effects of the rotation speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aqueous solution of Glycerol (Newtonian) and 0.2% aqueous solution of CMC (power-law fluid) were used in the experiments. A year later, another experimental study (Hansen and Sterri 1995) was undertaken to determine the effect of pipe rotation and pipe eccentricity on pressure losses in narrow annuli. The fluids used in this experiment were non-Newtonian and best fit the power law model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that for power-law fluids, when the flow regime is turbulent, the pressure loss increases with increasing pipe rotation, and when the flow regime is laminar, pressure drop decreases with increasing pipe rotation. Hansen and Sterri (4) experimentally investigated the effect of rotation on the frictional pressure loss in an annulus. Results indicated that pipe rotation increases the frictional pressure loss for low-viscosity fluids and decreases frictional pressure for high-viscosity shear thinning fluids.…”
Section: Introductionmentioning
confidence: 99%